Conjugated estrogens and bazedoxifene in minority populations: pooled analysis of four phase 3 trials. Issue 6 (June 2016) - Pinkerton, JoAnn V.; Pickar, James H.; Ryan, Kelly A.; Yu, Ching-Ray; Mirkin, Sebastian; Komm, Barry S.
Abstract: Objective: The aim of the study was to compare efficacy of conjugated estrogens (CE)/bazedoxifene (BZA) for treatment of menopausal symptoms and prevention of postmenopausal osteoporosis in minorities (black/Hispanic) versus whites. Methods: In a post hoc analysis, data were pooled from 3, 424 white or minority nonhysterectomized postmenopausal women randomized to CE 0.45 or 0.625 mg/BZA 20 mg or placebo in four double-blind, phase 3 Selective Estrogens, Menopause, and Response to Therapy (SMART) trials. Outcomes included hot flush frequency/severity (daily diary) in women with at least seven moderate-to-severe hot flushes per day (SMART-1, -2), vaginal cytology in women with at most 5% superficial cells (SMART-1, -3), lumbar spine and total hip bone mineral density (BMD) (SMART-1, -5), and the Menopause-Specific Quality of Life (MENQOL) questionnaire (SMART-1, -2, -3, -5). Results: The analysis included 2, 907 white (84.9%), 315 black (9.2%), and 202 Hispanic (5.9%) women. The reduction in hot flush frequency/severity versus placebo ( P  < 0.05; week 12) was similar in white and minority women. In both populations, both doses significantly ( P  < 0.05 vs placebo) improved MENQOL vasomotor function, sexual function, and total scores at 3 months; decreased the percentage of parabasal cells at 2 years; and increased the percentage of BMD responders at 12 and 24 months. Significant differential treatment effects by race/ethnicity were observed only for effects on vaginal superficial cells at month 24 and vaginal pH at month 3. Conclusions: Notwithstanding a limited sample size, CE/BZA had a similar and beneficial impact on hot flushes, MENQOL, and BMD in minorities and whites.